DISTANCE CALCULATION FROM WIND POWER INSTALLATIONS FOR REDUCTION OF INFLUENCE OF EFFECT OF SHADOWS-FLICKING ON HUMAN HEALTH - Запорожець, О.; Литвинюк, А. (Science-based technologies, 2012)
The main purpose of this work is to proof the necessity of standards for shadow-flicker as a negative impact on population living nearby wind farm. To define possible health problem that can be caused by flicker effect. Also this paper presents the calculation method of shadow length and the model of its spread by neighboring territo-ries. Recommendations development for establishing appropriate distance from wind turbine to receptor based on calculations and practical observations.